Organizacija in nadzor policije v izbranih državah: Zbornik raziskovalnega dela študentov Fakultete za varnostne vede in Pravne fakultete Univerze v Mariboru (University of Maribor Press, 2021)
Police Organization and Oversight in Selected Countries: Compilation of Research Papers Authored by the Students of the Faculty of Criminal Justice and Security and Faculty of Law of the University of Maribor. Chapters in this collection deal with the organization of the police and the regulation of police oversight in four selected countries: Canada, Italy, France and Croatia. The collection was created within the research project "Effectiveness of systemic control over the police in the field of respect for human rights and legal and professional standards of police work" (CRP V5-1942), which we began in November 2019 at the Faculty of Security Sciences. The research, co-financed by the Slovenian Research Agency and the Ministry of the Interior, focuses on the regulation and implementation of police oversight in Slovenia and includes a comparative view of police oversight systems in selected EU and non-European countries. Following the strategic guidelines of the faculty, the researchers invited students of undergraduate and postgraduate study programs to participate in the project. The analysis showed that selected countries have different models of organization and control over the police, characterized by a combination of different forms of internal and independent external control. Both the organization of the police and the system of its control in the selected countries differ in the degree of decentralization and dispersion, which is also characteristic of the regulation in Slovenia.